Transesterification Process of Biodiesel with Potassium Glycerolate Catalyst - Desi Erisna; Susila Arita; Fitri Hadiah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
The synthesis of potassium glycerolate catalyst from DES (Deep Eutectic Solvent â€“ K2CO3-glycerol) catalyst was carried out by heating process with various temperatures. The resulting catalyst product was analyzed and the characteristics of the best potassium glycerolate catalyst had conductivity 4482 microsiemens/cm, density 1.4858 g/cm3, Viscosity 121.574 cP, Freezing Point -8 celcius and pH 14. The best temperature in the manufacture of potassium glycerolate catalyst was at 150 celcius Alkaline pH is the main requirement to be a catalyst in the transesterification reaction. The trial results for the conversion of RBDPO to biodiesel with the optimum weight percent ratio of potassium glycerolate catalyst to RBDPO were 3.5%w, methanol 30%w, reaction temperature 65 celcius,Â reaction time 4 hours resulted in total glycerol content in biodiesel 0.2285%, acid value 0.15%, density 0.8705 gr/cm3, viscosity 5.22 Cst, conversion 96.77% and 97.81% methyl ester content and all of these parameters all meet the biodiesel standards set by SNI-7182: 2015.Â Keywords: Catalyst Characteristics, Potassium Glycerolate, Transesterification, Biodiesel